Thermoluminescence glow curves and deconvoluted glow peaks of Ge doped flat fibers at ultra-high doses of electron radiation - Alawiah, A.; Bauk, S.; Marashdeh, M.W.; Ng, K.S.; Abdul-Rashid, H.A.; Yusoff, Z.; Gieszczyk, W.; Noramaliza, M.N.; Mahdiraji, G.A.; Tamchek, N.; Muhd-Yassin, S.Z.; Mat-Sharif, K.A.; et al. (2015)
The behavior of Ge doped silica, SiO2 flat fibers (FF) irradiated with 2.5 MeV electron radiation at ultra-high dose (UHD) range, up to 1 MGy, has been investigated. The analyzed glow curves measured by the usage of the WinREMS software revealed that peak height and glow curve maximum temperature are highly dependent on the dose. The shape of the glow curves is constant with increasing dose. The supralinearity of all glow peaks increases to its f(D)(max), which occurs around 50 kGy. No saturation occurs at f(D)(max) and further increases in dose, up to 1 MGy, exhibits a significant decrease in f(D). The glow peaks 2 (230 degrees C) and 4 (290 degrees C), deconvoluted by the usage of WinGCF software, are the first-order kinetic peaks and can be used as the main dosimetric peaks for high-dose measurements between 1 and 50 kGy in an industrial environment. (C) 2015 Elsevier Ltd. All rights reserved.